The Kinocidin Interleukin-26 Shows Immediate Antimicrobial Effects Even to Multi-resistant Isolates - Hansen, Bjoern-Thore; Maschkowitz, Gregor; Podschun, Rainer; Fickenscher, Helmut (Frontiers in Microbiology, 2021)
The cationic proinflammatory cytokine Interleukin 26 (IL-26) shows antibacterial activity and inhibits the replication cytomegalovirus and hepatitis C virus. This study evaluates the early microbicidal activities of IL-26 against major bacterial species including multi-resistant variants and Candida albicans. Recombinant IL-26 was bacterially expressed and studied for its microbicidal effects in culture. We show that IL-26 has strong 90 % bactericidal activities against Enterococcus faecalis, Enterococcus faecium, Staphylococcus aureus, and Acinetobacter baumannii. Similarly, IL-26 sensitivity was also detectable in vancomycin-resistant Enterococcus species, methicillin-resistant Staphylococcus aureus, and carbapenem-resistant Acinetobacter baumannii clinical isolates. Additionally, a significant, albeit weak fungicidal effect against Candida albicans was observed. Activities against Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa were not detectable. The proinflammatory cytokine and kinocidin IL-26 shows strong bactericidal activities against Acinetobacter baumannii and, almost selectively, against Gram-positive bacteria.